Response to dabrafenib and trametinib combined with pembrolizumab in an elderly patient with lung adenocarcinoma of unknown primary harboring BRAF V600E mutation and high PD-L1 expression: a case report - Li, Nan; Hu, Jing; Bao, Guangjin; Cai, Zhigang (Frontiers in Immunology, 2025)
BRAF V600E mutation defines a rare but targetable subset of NSCLC. We report a 70-year-old non-smoking woman with unknown primary lung adenocarcinoma presenting with multistation mediastinal lymph-node metastases and massive malignant pleural and pericardial effusions. Molecular profiling showed BRAF V600E mutation and high PD-L1 expression(TPS 90%, CPS 95). The patient received combined dabrafenib, trametinib, and pembrolizumab with close safety monitoring, achieving rapid tumor control and complete remission by six months with manageable toxicity. This case suggests that early integration of PD-1 blockade with BRAF/MEK inhibition treatment may benefit selected patients and underscores the value of comprehensive molecular and immunohistochemical assessment to guide individualized therapy.